Familial Mediterranean fever (a periodic disease): The present-day view of the problem - Evgeny Stanislavovich Fedorov; S O Salugina; N N Kuzmina (Современная ревматология, 2013)
The paper deals with the most common classical autoinflammatory disease familial Mediterra-nean fever (FMF)/periodic disease. This is a monogenic hereditary disease caused by mutations with an autosomal recessive pattern of inheritance. The most common types of mutations are given. Hyperactivation of innate (antigen-specific) immunity is a basic pathogenic mechanism of the disease and IL-1ß is a leading mediator. FMF prominently occurs in certain ethnic groups (Sephardic Jews, Armenians, Turks, and Arabs). In spite of the fact that there may be multiple organ failure, 12-72-hour febrile fever episodes accompanied by the symptoms of peritonitis and/or pleuropericarditis. AA amyloidosis is the most serious complication of FMF. Colchicine therapy is a basic treatment for preventing this complication. In case of colchicine inef-fi-cacy/intolerance, other agents, including genetically engineered biological drugs (IL-1ß inhibitors, etc.), may be used.